1996
DOI: 10.1017/s0022215100135406
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymph node metastatic patterns of squamous carcinomas in the upper aerodigestive tract

Abstract: The radical neck dissection specimens of 384 ethnically Chinese patients with different primary squamous carcinomas in the head and neck region were studied. Over 50 per cent of the specimens showed metastatic disease at one level in the neck. For oral cavity carcinoma, the levels of metastasis frequently involved were I, II and III while for carcinoma of the oropharynx, hypopharynx and larynx, the levels were II, III and IV. Extracapsular spread was present in 112/384 of patients (29 per cent) and this increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
1
7

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 15 publications
7
43
1
7
Order By: Relevance
“…In regions where hook worm infestation is rampant, the use of antihelminthics may also be protective against oral cancer as hook worm can cause chronic iron deficiency anaemia. Few reports exist on diet which may protect against oral cancers [90,93]. This includes eating of diet rich in fresh fruits and vegetables [91,94].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In regions where hook worm infestation is rampant, the use of antihelminthics may also be protective against oral cancer as hook worm can cause chronic iron deficiency anaemia. Few reports exist on diet which may protect against oral cancers [90,93]. This includes eating of diet rich in fresh fruits and vegetables [91,94].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that clinical N0 necks have shown occult metastases in about 30% or higher, depending on the size, site of primary tumor and the histological diagnostic methods [21,118]. The great challenge that is being faced by the head and neck oncologists and surgeons is the correct identification of the subset of head and neck cancer patients, of which oral carcinoma constitutes about 30% [90], without micro metastases to the cervical lymph nodes. Clinical palpation of the neck combined with the radiological investigative tools has not been able to correctly identify all these patients [39,102,130].…”
Section: Justification Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Em muitos casos a principal queixa que motiva o paciente a procurar o médico é a presença de linfonodos cervical.Grande parte dos enfermos chegam no ato da primeira consulta com o tumor primário avançado e com linfonodos metástaticos no pescoço 2,7,[14][15][16] . Nossos pacientes apresentavam-se no diagnóstico inicial com o tumor Devido à rica rede de drenagem linfática da base de língua, o carcinoma epidermóide apresenta uma alta incidên-cia de metástase regional, comportamento agressivo, mais freqüentes com o aumento do estadiamento (T) 2,9,15,17 . A precoce invasão do sistema linfático cervical pode ser observada nos pacientes com pescoço clinicamente negativo e que são submetidos ao esvaziamento cervical.…”
Section: Discussionunclassified
“…Apesar de pouco freqüente foram achados linfonodos metástaticos no nível V, fatos estes equivalentes aos da literatura 10,11,17 . Ao correlacionarmos a presença de metástase para o pescoço e o fato da lesão primária ultrapassar ou não a linha média,observamos que na análise estatística não houve associação significante entre a presença de linfonodos metástatico regionais e o fato da lesão primária invadir a linha media da base de língua.…”
Section: Discussionunclassified